The Relationship Between Work-Family Conflict and Well-Being: The Mediator Effects of Emotional Exhaustion - Muhamad Zulfarhan, Amad Suhaimi (Universiti Malaysia Sarawak (UNIMAS), 2021)
The purpose of this study was to examine the mediating effects of emotional exhaustion in the relationship between work-family conflict and well-being among police officers. Questionnaire surveys were administered to police officers who works around Pulau Pinang with 187 questionnaires successively collected. Pearson correlation was used to test the hypotheses and the results show that work-family conflict and emotional exhaustion have a negative effect towards well-being among police officers. The result of the study also found that work-family conflict was positively affects emotional exhaustion among police officers. SPSS PROCESS version 3.5 by Andrew Hayes was used to test the mediating effect and the result shows that emotional exhaustion mediates the relationship between work-family conflict and well-being among police officers. The findings of the study may provide useful information and body of knowledge for both practitioners and future researchers for the purpose of improving current policy on work-life balance.